Form-function relations in cone-tipped stimulating microelectrodes - Yaeli, Steve; Binyamin, Einat; Shoham, Shy (Frontiers in Neuroengineering, 2009)
Metal micro-electrodes are widely used in neuroscience research, and could potentially replace macro-electrodes in various neuro-stimulation applications where their small size, specificity, and their ability to also measure unit activity are desirable. The design of stimulating microelectrodes for specific applications requires knowledge on how tip geometry affects function, but several fundamental aspects of this relationship are not yet well understood. This study uses a combined experimental and physical finite-elements simulation approach to formulate three new relationships between the geometrical and electrical properties of stimulating cone-tipped tungsten microelectrodes: 1. The empirical relationship between microelectrode 1kHz impedance and the exposed tip surface area is best approximated by an inverse square-root function (as expected for a cone-tipped resistive interface). 2. Tip angle plays a major role in determining current distribution along the tip, and as a consequence crucially affects the charge injection capacity of a microelectrode. 3. The critical current for the onset of corrosion is independent of tip surface area in sharp microelectrodes.